2019
DOI: 10.1128/msystems.00263-18
|View full text |Cite
|
Sign up to set email alerts
|

Designing Metabolic Division of Labor in Microbial Communities

Abstract: Microbes face a trade-off between being metabolically independent and relying on neighboring organisms for the supply of some essential metabolites. This balance of conflicting strategies affects microbial community structure and dynamics, with important implications for microbiome research and synthetic ecology. A “gedanken” (thought) experiment to investigate this trade-off would involve monitoring the rise of mutual dependence as the number of metabolic reactions allowed in an organism is increasingly const… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 108 publications
3
70
0
Order By: Relevance
“…MultiPlus [114] has two fixed objectives: minimizing the number of reactions and minimizing the exchanged metabolites, in a de novo synthesis pathway; starting from an hypergraph that integrates several GEM models. Following a MILP optimization approach, DOLMN [115] identifies communities able to survive under constraints (e.g. limited number of reactions) that are difficult to identify manually.…”
Section: Generic Methods Optimizing Pathway Distributions Have Been Amentioning
confidence: 99%
See 1 more Smart Citation
“…MultiPlus [114] has two fixed objectives: minimizing the number of reactions and minimizing the exchanged metabolites, in a de novo synthesis pathway; starting from an hypergraph that integrates several GEM models. Following a MILP optimization approach, DOLMN [115] identifies communities able to survive under constraints (e.g. limited number of reactions) that are difficult to identify manually.…”
Section: Generic Methods Optimizing Pathway Distributions Have Been Amentioning
confidence: 99%
“…At least 215 and 203 internal reactions to grow, respectively for 2 and 3 strain consortia. Loss one reaction is not compensated with adding one metabolite in the medium (nonlinear boundary) [115] Maximizing -4 E. coli case of study: -GR: 0.736 gDWh −1 -Strains ratio: Ec1-Ec2=50%, Ec3-Ec4=50%. Direct competition Ec1-Ec4 and Ec2-Ec3 -Gut microbiome case of study: values depending on fibre uptake from B. thetaiotaomicron:…”
Section: Human Gut Strains From Agora Collectionmentioning
confidence: 99%
“…Similarly, genome-scale metabolic models have been used to aide in the design of large scale communities by predicting metabolites that can be released by the producer without detriment to fitness, and conditions that encourage the establishment of stable communities (Pacheco et al, 2019). Thommes et al (2019) used genome scale metabolic models of E. coli to compute feasible division of labor strategies that could arise from an initial monoculture through loss of function in genes, giving insight into possible avenues for engineering community formation. Angulo et al (2019) demonstrated a mathematical method for identifying "driver species" in an ecological network.…”
Section: Modeling Approachesmentioning
confidence: 99%
“…In natural environments, microorganisms rarely live autonomously, but interact with other individuals to form complex communities, in which they secrete a variety of toxins to compete with each other, or share metabolites to mutually benefit their survival. Among a variety of modes of microbial interaction, metabolic division of labor (MDOL) is one of the most widespread phenomena, where distinct populations perform different but complementary steps of the same metabolic pathway [1][2][3][4] . MDOL controls numerous ecologically and environmentally important biochemical processes.…”
Section: Introductionmentioning
confidence: 99%